Effects of gibberellin on the activity of anammox bacteria. (1st November 2018) - Xu, Xianglong; Liu, Guo-hua; Fan, Qiang; Chen, Jinhui; Wang, Yuanyuan; Zhang, Ying; Yang, Yaqiong; Wang, Junyan; Zhang, Yuankai; Jiang, Hangcheng; Qi, Lu; Wang, Hongchen
Abstract: The enhancement of gibberellin (GA) on the activity of anaerobic ammonium oxidation(anammox) bacteria in short-term batch experiments(500 mL serum bottle) was studied in this paper. To make sure the accuracy of the data, each experiment group was conducted some statistical analysis. The results showed that GA played an important role in improving anammox activity when the GA dosage ranged from 0.1 to 1.5 mg L −1, and the total nitrogen removal rate (NRR) was increased by 34% when the GA dosage was 1 mg L −1 . The monitoring results of extracellular polymeric substances (EPS) and biomass of anammox bacteria indicated that GA addition improved the secretion of EPS and the biomass increasing, whose amount achieved maximum under the GA dose of 1 mg L −1 . Compared to the control test, the maximum improvement ratio of the EPS and biomass was 28.6% and 34%, respectively. In addition, the cloning results also indicated that the anammox bacterial community structure shifted in species level of Candidatus Brocadia genus during the experiment, and the most dominant anammox bacteria were Candidatus Brocadia fulgid. Highlights: The appropriate GA dosage can enhance the activity of anammox bacteria. The nitrogen removal efficiency increased by 34% when the GA dosage was 1 mg L −1 . Supplementary GA can increase EPS secretion and improve the growth of anammox bacteria. The most dominant anammox bacteria were Candidatus Brocadia fulgid in the anammox system supplemented with GA.